Exploring the Knowledge, Attitudes, and Practise of Healthy Eating Among Lactating Mothers in a Poor Rural Setting in North‐Western Ghana - Mildred Naamwintome Molle; Maximillian Kolbe Domapielle; Joshua Sumankuuro (Reproductive, Female and Child Health)
ABSTRACT Introduction Recognised as one of the most effective ways to guarantee positive maternal and child health outcomes, optimal nutrition for lactating mothers has received significant attention and investment both globally and locally. Despite this recognition, studies on maternal and child nutrition in Ghana have revealed that adherence to prescribed healthy eating regimens among lactating mothers in deprived settings has not received adequate scholarly attention. Thus, this study explores lactating mothers knowledge, attitudes, and practices regarding healthy eating to better understand the barriers to optimal nutritional outcomes for mothers and children, especially when chronic poverty is widespread. Methods This was a case study to explore the knowledge, attitudes, and practise of healthy eating among lactating mothers in the Wa West District. Convenience and purposive sampling procedures were followed to select lactating mothers and healthcare providers, respectively. Semi‐structured interviews were used to collect the data. The data were analysed using Anderson's behavioural model. The model offers a comprehensive analysis of factors—predisposition, enabling factors, and need for care—potentially influencing lactating mothers' knowledge, attitudes, and practise of healthy eating. Results The findings show that while lactating mothers in the district were aware of the importance of optimal nutrition for their health and wellbeing; food insecurity and pervasive poverty limit their opportunities to adhere to a balanced eating regimen. Conclusion An integrated development approach is needed to expand and sustain awareness of the importance of optimal nutrition for maternal and child health, improve local food production, and promote household economic empowerment.